Pengaruh Media Papan Kantong Pintar (PAKAPIN) Terhadap Hasil Belajar Peserta Didik Pada Materi Penjumlahan Di Kelas III SDN 1 Mata Ie Aceh Besar - Safhira Putri Nadilla; Linda Vitoria; Mislinawati Mislinawati (Universitas Syiah Kuala, 2023)
The purpose of this study was to determine the significance of the influence of PAKAPIN media on student learning outcomes on the additional material in class III SDN 1 Mata Ie Aceh Besar. The quantitative approach used in this research, the experiment is a type of research in the form of a one-shot case study. The sample in this research were all students of class III SDN 1 Mata Ie Aceh Besar totaling 22 people. The data collection technique in this research was a test in the form of an essay. The results of the research were analyzed using the right-hand t-test. The results showed that with a significant level of α= 0,05 and dk = (n-1) = (22-1) = 21 then the distribution list t with t(1- α)(n-1) = t(0,95)(21) is 1,72 because tcount ttable that is 5,88 1,72. So based on the results of this research, it can be concluded that PAKAPIN media has an influence on student learning outcomes in additional to the material. Thus, H0 is rejected as H1 is accepted, so the hypothesis in this research states that “there is a significant influence of PAKAPIN media on student learning outcomes on the summation material in class III SDN 1 Mata Ie Aceh Besar.